Development of automated storage and retrieval system (AS/RS) prototype - Abdul Halim, Hadzir (2010)
This report deals with the development of automated storage and retrieval system (AS/RS prototype. The original idea for this project is to help people which working in warehouse such as operator who wants to store and retrieve the drawer (unit loads) into and from cabinet (storage structure). The AS/RS have been widely used in distribution and productions environment. The AS/RS consists of racks and cranes (storage/retrieval machine, lifter and drawer picker) where the racks served by cranes running through aisles between the racks and it’s fully automated where it capable of handling drawer without interference of an operator. The development accentuate on mechanical approach. The prototype three-dimensional solid modelling of AS/RS was developed using the computer-aided drawing software. For this project PIC18F452 microcontroller was chosen as a control system. Other than that, stepper motor was used to move the storage/retrieve (S/R) machine during to store and retrieve the drawer. A program in mikroElektronika (MikroC) is written and developed to correspond with the microcontroller to move the stepper motor according to plan sequences. The real time testing was done in order to know the performance of fabricated prototype. The transaction time during depositing and retrieving the drawer into and from cabinet is successfully recorded. The development in phrase can be concluded as an innovation of design and successfully fabricated.